The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/medicina56110581
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Reporting Clinical and Epidemiological Data in Urology: Local Experiences and Insights from the International Literature

Abstract: Pathologies of the genito-urinary tract are responsible for a considerable disease burden worldwide, leading to significant losses of income, lost working days, increased expenditures for national healthcare systems, and decreased quality of life (QoL) in the affected patients. Among these diseases, infections and malignancies in this anatomical region are some of the most important illnesses in human medicine; nevertheless, benign prostate hyperplasia (BPH), erectile dysfunction, hypospadias, urinary incontin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…We found that Escherichia coli was the most prevalent pathogen in both sexes regarding isolated pathogens, which is in line with previous reports [ 1 , 7 , 26 , 28 , 33 , 34 , 35 ]. However, the risk of IHM was associated with Staphylococcus aureus , but the risk decreased with other isolated pathogens, which is also observed among patients with COPD and type 2 diabetes mellitus [ 7 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We found that Escherichia coli was the most prevalent pathogen in both sexes regarding isolated pathogens, which is in line with previous reports [ 1 , 7 , 26 , 28 , 33 , 34 , 35 ]. However, the risk of IHM was associated with Staphylococcus aureus , but the risk decreased with other isolated pathogens, which is also observed among patients with COPD and type 2 diabetes mellitus [ 7 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Urinary tract infections (UTIs) are considered the third most common type of infections [ 1 , 2 ]. UTI incidence increases with age and is an important cause of antibiotic use, morbidity, and mortality in older adults [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Reporting of epidemiological data in urology and urinary tract infections are crucial to influence the development of therapeutic guidelines for UTIs and also the relevant stakeholders and government representatives often base their decisions on published evidence. 10 According to the Center for Disease Control and Prevention (CDC), UTIs are the most common bacterial infection requiring medical care, resulting in 8.6 million ambulatory care visits in 2007, 23% of which occurred in the emergency department. 11 An estimated 50% of women report having had a UTI at some point in their lives and 8.3 million office visits and more than 1 million hospitalizations, for an overall annual cost of more than $1 billion.…”
Section: Introductionmentioning
confidence: 99%